Sibling Screening in Pediatric Brucellosis - Özen, Seval; Üçkardeş, Fatih; Alev, Curet; Uygun, Hatice; Erdem, Nurettin; Turgut, Mehmet (Journal of Pediatric Infectious Diseases, 2022)
Objective Routine screening of household members of index cases is a priority in regions where brucellosis is endemic. This study aimed to identify seropositive and seronegative pediatric patients by screening the siblings of our pediatric patients diagnosed with brucellosis (index cases) and to investigate the relationships among these groups by comparatively evaluating their demographic, epidemiological, clinical, and laboratory characteristics.Methods Eighty-five pediatric household members of 59 pediatric patients diagnosed with acute brucellosis were evaluated. A total of 144 children were included in the study.Results Among 85 pediatric household members, 34 (40%) children were seropositive and 51 (60%) were seronegative. The predominant clinical symptom was arthralgia (81.4%), and the main finding was abnormal liver function tests (LFTs). The most frequent osteoarticular involvement was monoarticular arthritis (88%). Index cases and seropositive patients showed significantly greater elevations in LFTs compared with seronegative patients (p < 0.001 and p < 0.001). C-reactive protein values of index cases and seropositive patients were significantly higher compared with seronegative patients (p < 0.001 and p = 0.001). Neutrophil and platelet counts of index cases were significantly lower than those of seronegative patients (p = 0.017 and p = 0.002). Index cases and seropositive patients were given treatment, and after follow-up of at least 1 year, none of the seropositive patients relapsed, but relapse occurred in nine (15.3%) children from the index group. Two (3.9%) seronegative patients were diagnosed with acute brucellosis.Conclusion Additional cases of brucellosis can be detected by screening household members of index cases in endemic areas. Elevations in LFTs when detected early in the asymptomatic period may provide a clue for brucellosis.
Keywords: brucellosis; screening; seropositive asymptomatic; index case